ORAL SIGNS OF LEUKEMIA AND DENTAL MANAGEMENT – literature data and case report. - Elitsa G. Deliverska; Assya Krasteva (Journal of IMAB, 2013)
A The oral signs and symptoms may be reflect a undetected serious systemic diseases. Depending on the oral manifestation the dentists and physicians make attention and focusing on specific diagnoses. In some cases oral involvement may be frequently herald the onset of the disease which requires the dentists to better knowledge of changes in the oral cavity. In the oral cavity local symptoms and findings of leukemia include paleness of the oral mucosa with gingival bleeding that develops into painless gingival hyperplasia, petechiae, hemorrhages, and ulcerative necrotic lesionsBecause of their clinical importance, all such lesions deserve the full attention of the dental doctors. The aim is to evaluate in detail the oral complications of leukemia at initial presentation and present a clinical case of 54 old female with oral manifestation as initial signs of the disease.